AS INTERFACES DAS TEOLOGIAS LATINO-AMERICANAS: APROXIMAÇÕES E DISTANCIAMENTOS ENTRE A TEOLOGIA DA LIBERTAÇÃO E A TEOLOGIA DA MISSÃO INTEGRAL - CAPPELLETTI, PAULO (2018)
The analysis objects of this thesis are the interfaces between the two Latin American theologies, the Liberation Theology and the Theology of Integral Mission. Theses theologies have in common the historical-social context of the second part of the twentieth century, when the world has undergone profound social, political, economic and religious changes. The world was divided into two ideologies, the capitalist and the Marxist, but also into rich countries and underdeveloped countries, poor and dependents. In Latin American, it was the rural exodus and industrialization that means the large displacement of the rural population to the big cities and, consequently, the growth and the visibilization of the poor people on the edge of towns. These factors influenced directly on the birth of the Latin American theologies: Liberation Theology (LT), which has its origin in the Protestant field, of ecumenical line, and Catholic field; and the Theology of Integral Mission (TIM), which is from evangelical field, also known as “evangelicals”, that sought establish a distance from fundamentalist protestant world. In the studies field of Latin America theologies, there are more about the LT than about TIM and almost nothing about the relation between them. Both have in common the purpose of to help or lead, in name of God, of Church or of poor people, the liberation of poor from the sufferings of poverty and oppression. However, these theologies saw themselves as conflicting or in large difficult to establish a dialogue between them. Therefore, the scope of this thesis is understand exactly “The interfaces of the Latin American theologies”, in particular its origins, its main convergences - notion of incarnation in history, hermeneutics, Kingdom of God, liberation of the poor - and differences - the place or not of Marxism, the poor as historical individual or the Church.